2006
DOI: 10.1086/507710
|View full text |Cite
|
Sign up to set email alerts
|

American Tegumentary Leishmaniasis: Is Antimonial Treatment Outcome Related to Parasite Drug Susceptibility?

Abstract: Antimony insensitivity might occur in a stepwise fashion (first to SbV and then to SbIII). Our data question the definition of true parasite resistance to antimonials. Further studies of treatment efficacy should apply standardized protocols and definitions and should also consider host factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
102
2
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(113 citation statements)
references
References 31 publications
4
102
2
5
Order By: Relevance
“…Patients who experienced treatment failure in Peru were more likely to have had a short disease duration, have more than one CL lesion, have either Leishmania peruviana or Leishmania braziliensis isolated, and have lived in an area of endemicity for less than 72 mo (34). In vitro susceptibility to antimony was not determined, but a related study found no correlation between parasite resistance and clinical outcome to antimonial therapy (35). Detailed epidemiological work is underway to explore the relationship between arsenic exposure and antimonial treatment failure in VL in Bihar, including assessment of established clinical risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Patients who experienced treatment failure in Peru were more likely to have had a short disease duration, have more than one CL lesion, have either Leishmania peruviana or Leishmania braziliensis isolated, and have lived in an area of endemicity for less than 72 mo (34). In vitro susceptibility to antimony was not determined, but a related study found no correlation between parasite resistance and clinical outcome to antimonial therapy (35). Detailed epidemiological work is underway to explore the relationship between arsenic exposure and antimonial treatment failure in VL in Bihar, including assessment of established clinical risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, different epi-phenotypes to which the parasites could have developed specific adaptations might remain hidden in the in vitro Sb V susceptibility assays, but interfering with the gene expression patterns. For instance, (i) the variable adaptation to the macrophage effectors in the immunological context of the clinical infection (absent in the in vitro susceptibility assays) or (ii) the resistance to the reduced form of the drug, Sb III (Yardley et al 2006;Rijal et al 2007). These epi-phenotypes would explain the incongruences between the parasites' in vitro Sb V resistance and chemotherapy failure reported elsewhere (Yardley et al 2006;Rijal et al 2007) and illustrated in Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…Isolates were essentially obtained before treatment of patients, typed by PCR-RFLP analysis of hsp70 and cpb genes (Garcia et al 2005) and tested as intracellular amastigotes for their in vitro susceptibility to Sb V (Yardley et al 2006) (see Table 1 for summary of isolate features). Promastigote forms were grown at 24°C in a biphasic medium consisting of rabbit blood agar overlaid with medium 199 (M199; Sigma) containing 20% heat-inactivated fetal bovine serum (FBS; Lonza Bioscience), 25 mM Hepes (pH 7·4), 100 units/ml penicillin and 100 μg/ml streptomycin (Lonza).…”
Section: Parasites and In Vitro Culturementioning
confidence: 99%
See 1 more Smart Citation
“…67 Recently a study reported 7% of patients unresponsive to SbV. 68 Unresponsiveness could be caused by the use of subtherapeutic doses and substandard drugs, patient non-compliance with the treatment regimen, immunosuppression (e.g., because of HIV infection), and, of course, the real emergence of drug-resistant parasite strains. Of note is that, whereas SbV-resistant strains of L. For patients unresponsive to antimony (e.g., ML patients), amphotericin B deoxycholate (Fungizone , Bristol Myers Squibb, New York, NY) is the second-line drug in Bolivia.…”
Section: Disease Distribution Notification and Incidencementioning
confidence: 99%